Covid-19 and the current scenario of the City of Castanhal – PA, Brazil (Research, Society and Development, 2020)
COVID-19, a disease discovered on December 31, 2019, has symptoms similar to those of a common flu, and gradually impacts lives in the worldwide population . A study carried out by the Universidade Federal de Pelotas (Federal University of Pelotas) (UFPEL), identified 11 cities located in the northern region with a high percentage of contamination by COVID-19, the municipality of Castanhal, located in the northeast of the State of Pará, Amazon, Brazil, stands out among the Brazilian cities with one of the highest contamination rates, being placed in third place in the national ranking of the prevalence index. Therefore, this article aims to verify the COVID-19 index in Castanhal-Pará, Brazil. Methodologically, data were collected on the website of the State Department of Public Health of Pará (SESPA), in addition to bibliographic research, with a quantitative and qualitative approach that enfolds the involvement of mixed methods. In the results, there was an increase in the rate of confirmed cases as well as deaths and recoveries. From just 01 confirmed case on March 27, 2020, the municipality went to 1,215 confirmations of COVID-19 until June 12, 2020. In addition, the strategic function of the city of Castanhal was verified for the functioning of part significant number of municipalities in the northeast of Pará. It is concluded that several state and municipal measures were taken, in an attempt to face COVID-19, but continuous care is needed, both by the population and by the government in the fight against the new coronavirus.